DAMPAK KENAIKAN HARGA BBM TERHADAP INFLASI DAN DAYA BELI MASYARAKAT DI PROVINSI KEPULAUAN RIAU - Kevin Andika Putra; Zahmil Husein; Siska Aulia Putri; Wahjoe Pangestoeti (PT. Hasba Edukasi Mandiri, 2025)
The increase in Fuel Oil (BBM) prices in the Riau Archipelago Province (Kepri) has had a significant impact on inflation and the purchasing power of the community. This study aims to analyze the impact using a qualitative approach by utilizing data from social assistance programs, transportation subsidies, market operations, and BBM distribution supervision. The findings indicate that the increase in BBM prices contributes to high inflation, leading to higher prices of essential goods, transportation, and energy. The community, especially low- and middle-income groups, experiences a significant decline in purchasing power, forcing them to reduce spending on non-essential goods. The government has taken various measures, such as providing subsidies, holding affordable markets, and overseeing distribution to mitigate these impacts. However, these policies need to be strengthened with a more integrated approach to address the long-term effects of BBM price fluctuations.